IMPACT OF MULTIPLE SCLEROSIS ON COGNITIVE FUNCTION: MECHANISMS AND INTERVENTIONS - Souza, MARIA HEDDUARDA COSTA DE; SANTOS, MARIA LUÍSA SILVA; RODRIGUES, SARA CRISTINA JUSTINO; Oliveira, Yasmin Daiane Silva de; Nunes, Poliana Lucena; Filha, Ana Júlia Andrade Batista (CIPEEX, 2025)
Multiple Sclerosis (MS) is an autoimmune neurological disease that affects the central nervous system, causing inflammation. It mainly affects young adults and is more prevalent in women. Physical symptoms vary, including fatigue, muscle weakness, and sensory changes. Cognitive functions such as memory, attention, and processing speed are essential for daily activities and are often compromised in MS patients. The study aims to investigate how the disease affects memory and reasoning, in addition to available neurological rehabilitation techniques. A literature review was conducted using Google Scholar, SciELO, and PubMed. Full-text articles published between 2020 and 2025, in Portuguese and English, were selected. Studies indicate that more than 50% of patients have some degree of cognitive dysfunction, varying according to the disease subtype. The most affected areas include working memory and processing speed, associated with structural changes such as brain atrophy and white matter lesions. Neuropsychological assessment is essential for early diagnosis. Cognitive rehabilitation, through specific training and digital technologies, combined with the support of neuropsychologists, occupational therapists, and speech therapists, has shown promising results in improving functional abilities. Research on neuroprotection and remyelination continues, reinforcing the importance of a multidisciplinary approach focused on quality of life and autonomy. Neuropsychological rehabilitation is essential to alleviate the cognitive deficits of MS, promoting functionality and autonomy.